MANAJEMEN KEPEMIMPINAN DALAM MENINGKATKAN MUTU PENDIDIKAN MELALUI MANAJEMEN BERBASIS SEKOLAH - Lukman Hakim (Pedir Research Institut, 2022)
Improving the quality of education is one of the urgent problems and it is deemed necessary to get serious attention and handling from various related parties. This is closely related to school leadership and management. In addition, in improving the quality of education, all aspects of a school must be considered, both input, process, and output. The quality of education is deemed necessary to make improvements and changes in various sectors including leadership and management. The success of a school will only be able to carry out effective management, effective management can only be carried out by professional leadership. Things that need to be done by leaders as managers are: planning and evaluating, organizing, directing and monitoring, and monitoring continuous evaluation for further action. This study describes leadership management in improving the quality of education through School-Based Management which is applied at the UPT Education Unit of SDN Pulokerto Kraton Pasuruan Regency with the research focus: How are the results of principals' leadership in improving the quality of education through school-based management, How are the supporting factors and inhibiting factors in improving the quality of education through school-based management? improve the quality of education through School-Based Management. This study uses a qualitative research approach with the type of case study. Research data obtained by involved observation techniques, in-depth interviews and documentation. Key informants in this study, principals and teachers.